Efektivitas Penggunaan Madu Topikal Terhadap Penyembuhan Luka Kaki Diabetik - Karyatin Karyatin; Putri Dela Cahyanti (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Diabetes mellitus is a health problem that can cause several complications, one of which is diabetic foot ulcers. Diabetic foot wounds are injuries that occur in people with diabetes mellitus. According to the International Diabetes Federation (2019), there are 40-60 million people with diabetes mellitus who experience diabetic foot ulcers in the world. Wound care for diabetic foot ulcers can reduce the increase in the number of diabetic patients with foot ulcers. One alternative treatment method that has been used until now is wound care using honey. The purpose of this study was to determine the effectiveness of using honey for diabetic foot wounds. This research method uses the Literature review method using 5 national and 2 international journals by searching through the Google Schoolar, Sciene Direct and Publish or Perish databases in the 2016-2021 range using PICOST analysis. The results of the seven studies that have been carried out in a literature review, there is an effect of giving honey on the healing of diabetic foot wounds. The honey used is real honey and mixed honey, both honeys have been proven to be effective in the wound healing process because honey can accelerate the growth process of granulation tissue in diabetic foot wounds properly and can maintain wound moisture.